STUDI INTEGRATIF TEOLOGI DAN MEDIA SOSIAL - Made Nopen Supriadi; Yohanes Dian Alpasa (Phronesis: Jurnal Teologi dan Misi, 2022)
Today's technological developments have provided effortless access for the current generation of Generation Z to get the information they need. However, the problem occurs when Generation Z misreads information, one which is information related to the doctrines of the Christian faith. This condition challenges teachers to make Z able to fill the social media space with the correct teachings. Therefore, it is necessary to formulate theological thoughts that are indeed following the development of today's social media. Through an integrative study approach between theology and social media and phenomenological studies related to the problems that arise. So this research produces a combination of theology and social media that contributes to social media content filled with true theology and theology that is open in general because social media bridge it. This research contributes so that Generation Z is not trapped in wrong doctrines in social media.